TURKIC LOANWORDS IN ENGLISH: A LEXICOGRAPHICAL JOURNEY - Xalilullo Qodirov (Лучшие интеллектуальные исследования, 2023)
Abstract: This article embarks on a lexicographical journey to uncover Turkic loanwords in the English language. It explores their historical roots, revealing their introduction through centuries of cultural exchanges, trade, and encounters. Notable examples like "bazaar," "pasha," and "yogurt" serve as milestones. The article also delves into the meticulous codification of these words in dictionaries, showcasing the work of lexicographers who preserve their etymology and usage.